A Tractable Line-of-Sight Product Channel Model: Application to Wireless Powered Communications - López-Martínez, Francisco Javier; Moreno-Pozas, Laureano; Fernández-Plazaola, Unai; París-Ángel, José Francisco; Martos-Naya, Eduardo; Romero-Jerez, Juan Manuel (My University, 2018)
We here present a general and tractable fading model for line-of-sight (LOS) scenarios, which is based on the product of two independent and non-identically distributed κ- μ shadowed random variables. Simple closed-form expressions for the probability density function and cumulative distribution function are derived, which are as tractable as the corresponding expressions derived from a product of Nakagami-m random variables. This newly proposed model simplifies the challenging characterization of LOS product channels, as well as combinations of LOS channels with non-LOS ones. Results are used to analyze performance measures of interest in the context of wireless powered communications.
Keywords: Sistemas de comunicaciones inalámbricos; Fading; Channel modeling; Wireless powered communications